Alternative in overcoming anxiety in mathematics learning - Mohd. Rameli, Mohd. Rustam (2013)
Math anxiety is an affective variable that directly or indirectly impacts the life of students and teachers who apply mathematical knowledge and skills in everyday life. The negative effects of math anxiety include disturbance during the process of learning mathematics, career selection, and survival. Studies have recommended various methods to minimize the negative effects of math anxiety. This paper also discusses few alternatives to reduce the negative effects of math anxiety on school students. The alternatives include inculcating positive thinking against negative talk and building support group; building assessment strategies, using effective learning style, minimizing the element of competition, active teacher and parental support and classroom structure. This study concludes that math anxiety can potentially disturb the learning process itself. Therefore, all stakeholders including teachers, parents, and the students themselves need to look for alternatives to overcome the math anxiety. This may help in assuring effective learning for students in mathematics.